2018
DOI: 10.3892/or.2018.6383
|View full text |Cite
|
Sign up to set email alerts
|

Identifying genes as potential prognostic indicators in patients with serous ovarian cancer resistant to carboplatin using integrated bioinformatics analysis

Abstract: Serous ovarian cancer (SOC) accounts for >50% of all epithelial ovarian cancers. However, patients with SOC present with various degrees of response to platinum-based chemotherapy and, thus, their survival may differ. The present study aimed to identify the candidate genes involved in the carcinogenesis and drug resistance of SOC by analyzing the microarray datasets GDS1381 and GDS3592. GDS1381 and GDS3592 were downloaded from the Gene Expression Omnibus database (). A total of 219 differentially expressed gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 42 publications
3
34
0
Order By: Relevance
“…Moreover, proteins that maintain chromosome condensation (the condensin complex) are also elevated (3 genes; marked by ***, Supplemental Table S5). Interestingly, a recent study comparing differentially expressed genes between normal human ovarian tissue and ovarian cancer, and carboplatin-sensitive and resistant ovarian tumors [46], identified a similar set of genes identified in our canine study; of the 5 top genes identified in their study (GNAI1, NCAPH, MMP9, AURKA and EZH2), three were identified in our study (NCAPH, AURKB (rather than AURKA) and EZH2). Taken together, our work suggests that MDR development in these 4 canines is associated with impaired APC activity.…”
Section: A 290 Gene Set Overexpressed >3-fold In Tumour Vs Control Wasupporting
confidence: 80%
See 2 more Smart Citations
“…Moreover, proteins that maintain chromosome condensation (the condensin complex) are also elevated (3 genes; marked by ***, Supplemental Table S5). Interestingly, a recent study comparing differentially expressed genes between normal human ovarian tissue and ovarian cancer, and carboplatin-sensitive and resistant ovarian tumors [46], identified a similar set of genes identified in our canine study; of the 5 top genes identified in their study (GNAI1, NCAPH, MMP9, AURKA and EZH2), three were identified in our study (NCAPH, AURKB (rather than AURKA) and EZH2). Taken together, our work suggests that MDR development in these 4 canines is associated with impaired APC activity.…”
Section: A 290 Gene Set Overexpressed >3-fold In Tumour Vs Control Wasupporting
confidence: 80%
“…Previous work has also demonstrated APC substrates to be elevated in cancer cells [80,82]. Furthermore, recent work comparing differential gene expression in drug sensitive and resistant ovarian tumor datasets [46] revealed a similar collection of genes that were identified by us; half of the 30 highly connected nodes they identified were associated with APC function or substrates. Consistent with these observations, remission and relapse of canine 4 following metformin treatment identified 27 genes that were upregulated in the tumor, downregulated following metformin treatment, then upregulated again following relapse (Fig.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Therefore, this approach has been applied extensively to the diagnosis and treatment of human cancers. For example, researchers believed that GNAI1, NCAPH, MMP9, AURKA and EZH2I were identified as the key molecules in patients with serous ovarian cancer resistant to carboplatin using integrated bioinformatics analysis (Zhan et al 2018). COL1A2 as a diagnostic biomarker was highly tissue specific and was expressed in human gastric cancer by integrating bioinformatics and meta-analysis (Rong et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The identification of novel biomarkers is currently an efficient approach for large-scale screening and diagnosis (Liu et al 2018, Zhan et al 2018. Therefore, we performed analysis of 11 original microarray data to identify DEG response to different heavy metals in the present study.…”
Section: Introductionmentioning
confidence: 99%